The Effect of Export and Import on Economic Growth in Indonesia - Millia, Heppi; Syarif, Muh.; Adam, Pasrun; Rahim, Manat; Gamsir, Gamsir; Rostin, Rostin (International Journal of Economics and Financial Issues, 2021)
This research aims to examine the effect of export and import on economic growth. The data used are time series data consisting of export, import and economic in period 2004Q1-2018Q1. The test results using the autoregressive distributed lag (ARDL) model indicates that in the short and long run, there is the effect of export and import on economic growth. In the long run, every 1% of the decline in import lead to the 1.17% increase of the economic growth, while 1% increase in export lead to the 1.83% increase of the economic growth. Keywords: Export, import, economic growth, ARDL model JEL Classifications: C130, F140, F430 DOI: https://doi.org/10.32479/ijefi.11870